ChemInform Abstract: Coupling Reaction of Enol Derivatives with Silyl Ketene Acetals Catalyzed by Gallium Trihalides. Issue 51 (5th December 2016) - Nishimoto, Yoshihiro; Kita, Yuji; Ueda, Hiroki; Imaoka, Hiroto; Chiba, Kouji; Yasuda, Makoto; Baba, Akio
Abstract: The title preparation of α‐alkenyl esters has a broad substrate scope.